2020
DOI: 10.1136/gutjnl-2019-319565
|View full text |Cite
|
Sign up to set email alerts
|

Adenoma detection by Endocuff-assisted versus standard colonoscopy in routine practice: a cluster-randomised crossover trial

Abstract: ObjectiveEndocuff Vision (ECV) is the second generation of a device designed to improve polyp detection. The aim of this study was to evaluate its impact on adenoma detection rate (ADR) in routine colonoscopy.DesignThis cluster-randomised crossover trial compared Endocuff-assisted (ECV+) with standard (ECV-) colonoscopy. Two teams of 11 endoscopists each with prior ECV experience, balanced in terms of basal ADR, gender and case volume were compared. In randomised fashion, the teams started with ECV+ or ECV- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 25 publications
(47 reference statements)
2
43
1
Order By: Relevance
“…The MAP was not clinically and statistically different for ECV group when compared to HD colonoscopy (MD: 0.14, 95 % CI–0.01–0.28, p = 0.06, I 2 = 53.1 %) ( Supplementary Fig. 1d ) 15 23 28 35 .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The MAP was not clinically and statistically different for ECV group when compared to HD colonoscopy (MD: 0.14, 95 % CI–0.01–0.28, p = 0.06, I 2 = 53.1 %) ( Supplementary Fig. 1d ) 15 23 28 35 .…”
Section: Resultsmentioning
confidence: 93%
“…Twelve RCTS were included after rigorous screening of abstracts and full texts with a total of 8638 patients (4285 in HD group, 4353 in Endocuff group) ( Fig. 1 ) 15 25 26 27 28 29 30 31 32 33 34 35 . All studies were published after 2014.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a debate has started regarding whether the effectiveness of EV differs depending on the individual endoscopist. Some data suggested that "high detectors" obtained no additional bene t from using the Endocuff [39]; however, in a cluster randomized crossover trial performed in 2020, a subanalysis suggested that "high detectors" (de ned as those with an ADR>25%) had a signi cantly higher ADR when using EV (mean difference 10.3%, p=0.001), while low detectors had a nonsigni cant mean difference (6.7%, p=0.11) [40]. Our study did not allow us to explore this hypothesis due to the sample size and the fact that all endoscopists had ADRs above 40%, which may explain our results.…”
Section: Discussionmentioning
confidence: 99%
“…Distal attachment ▶ ▶ Table 2 Crude and adjusted odds ratios for adenoma and sessile serrated adenoma detection by selected variables. devices are simple to use [12][13][14], and ECV in particular is efficacious in improving ADR [20][21][22][23]. No large "real-world" studies have assessed the effectiveness of ECV.…”
Section: Original Articlementioning
confidence: 99%